2012
DOI: 10.1038/jes.2012.69
|View full text |Cite
|
Sign up to set email alerts
|

Impact of NOx emissions reduction policy on hospitalizations for respiratory disease in New York State

Abstract: To date, only a limited number of studies have examined the impact of ambient pollutant policy on respiratory morbidities. This accountability study examined the effect of a regional pollution control policy, namely, the US Environmental Protection Agency's (EPA) nitrogen oxides (NO(x)) Budget Trading Program (NBP), on respiratory health in New York State (NYS). Time-series analysis using generalized additive models was applied to assess changes in daily hospitalizations for respiratory diseases in NYS after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
13
0
3
Order By: Relevance
“…93,94 Following the implementation of EPA’s nitrogen oxides (NOx) Budget Trading Program policy, there also were significant reductions in mean ozone levels ( − 2% to − 9%) throughout NY state and post-intervention declines in respiratory admissions were observed. 95 The Clean Air Act and its amendments have reduced vehicle-related pollutants significantly. 96 These examples and others highlight the opportunities that exist to decrease pollutant impacts on allergic lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…93,94 Following the implementation of EPA’s nitrogen oxides (NOx) Budget Trading Program policy, there also were significant reductions in mean ozone levels ( − 2% to − 9%) throughout NY state and post-intervention declines in respiratory admissions were observed. 95 The Clean Air Act and its amendments have reduced vehicle-related pollutants significantly. 96 These examples and others highlight the opportunities that exist to decrease pollutant impacts on allergic lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, recent research by Lin et al (2013) on the effect of the NO x Budget Trading Program to improve regional air quality in the Eastern United States has found that ozone levels were decreased by 2-9% in New York State during the period [2004][2005][2006]. This resulted in fewer hospital admissions for respiratory disease (up to 11% lower in some counties, including the New York City metropolitan area), although some other counties showed an increase of nearly 18%.…”
Section: United States Clean Air Act and Related Air Pollution Contromentioning
confidence: 99%
“…The reliance on existing datasets did not always make it possible rule out alternative explanations. For example, one study of the impact of the EPA (Environmental Protection Agency) NOx (mono-nitrogen oxides) Budget Trading Program reviewed New York state hospital discharge records for respiratory diagnoses after the implementation of the program (Lin 2013), but could not control for the simultaneous implementation of the state’s clean indoor air law, although implementation of this law would also be expected to affect levels of respiratory disease [ 18 ]. In addition, the use of existing datasets to measure exposures meant that the policy intervention may have had additional effects that could not be measured with the data that were available to researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the included studies relied on environmental measures, and two used measures of effects on humans. Seven of the 11 studies reviewed data from before and after the implementation of the intervention(s) [ 16 , 19 24 ] and the remainder included only post-implementation measures [ 18 , 25 27 ].…”
Section: Resultsmentioning
confidence: 99%